1978
DOI: 10.1128/iai.22.1.266-274.1978
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Levan by Actinomyces viscosus

Abstract: Actinomyces viscosus ATCC 15987 was examined for its ability to hydrolyze its own levan. Washed whole cells and an ammonium sulfate fraction from cell-free culture fluids were shown to possess levan hydrolase activity. Analyses of reaction mixtures by gel filtration and thin-layer chromatography demonstrated that the product of levan hydrolysis was free fructose. The cell-associated and extracellular enzyme preparations also hydrolyzed inulin and the levans synthesized by Aerobacter levanicum and Bacillus subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The presence of fructan in dental plaque has been demonstrated by several authors (19,23,24). Fructan in dental plaque is synthesized extracellularly by many oral bacteria such as Streptococcus salivarius (11,12,14,16,27,31), Streptococcus mutans (3,4,5,8,11), Actinomyces viscosus (19,20,25,26,28,29,36,39), and Rothia dentocariosa (21). However, the fructan produced in dental plaque is not homogeneous.…”
Section: P-(26)-fructofuranosidasementioning
confidence: 99%
See 3 more Smart Citations
“…The presence of fructan in dental plaque has been demonstrated by several authors (19,23,24). Fructan in dental plaque is synthesized extracellularly by many oral bacteria such as Streptococcus salivarius (11,12,14,16,27,31), Streptococcus mutans (3,4,5,8,11), Actinomyces viscosus (19,20,25,26,28,29,36,39), and Rothia dentocariosa (21). However, the fructan produced in dental plaque is not homogeneous.…”
Section: P-(26)-fructofuranosidasementioning
confidence: 99%
“…On the other hand, several studies have shown that fructans synthesized in dental plaque are degraded or metabolized by some of the dental plaque organisms (7,15,18,23,37,41). Several streptococcal strains in human dental plaque have been reported to hydrolyze levan produced by S. salivarius, S. mutans, and A. viscosus (7,23,25,37,41). The latter strain degraded its own levan (25).…”
Section: P-(26)-fructofuranosidasementioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria that produce fructans also produce enzymes that degrade these polymers (11). Previous studies have indicated that oral Actinomyces have the capacity to hydrolyze a variety of fructans via enzymes that specifically break down (i) only levans, (ii) only inulins, sucrose, and raffinose, but not levans; or (iii) levans, inulins, sucrose, and raffinose (40,62). Enzymes that can attack levans, regardless of whether they attack multiple other fructosides, are often referred to as levanases.…”
mentioning
confidence: 99%